Refinement of the Microwave-Assisted Polyol Process for the Low-Temperature Synthesis of Intermetallic Nanoparticles - Teichert, Johannes; Heise, Martin; Chang, Jen-Hui; Ruck, Michael (European Journal of Inorganic Chemistry, 2017)
The microwave-assisted polyol process was applied to synthesize phase-pure micro- or nanocrystalline intermetallic phases in the systems T–M (T = Co, Ni, Rh, Pd, Ir, Pt and M = Sn, Sb, Pb, Bi). Reaction temperatures range between 240 and 300 °C, and reaction times of a few minutes up to 1 h are sufficient. For optimization of the syntheses, the reaction temperature, reaction time, and metal precursors were changed. To obtain phase-pure samples the process was further modified by the addition of potassium hydroxide, oleylamine, or oleic acid. Single-phase powders of a variety of intermetallic compounds were synthesized. Although not stable at the temperature of synthesis, high-temperature phases are accessible as well. The microwave-assisted polyol process opens up the possibility to synthesize intermetallic compounds through a fast and easily applicable one-step route, without utilization of strong and often toxic reducing agents.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Intermetallic phases; Microwave chemistry; Nanoparticles; Polyol process; Reduction